Atherogenic Index of Plasma (AIP) as a Long‐Term Prognostic Factor Following CABG: Unveiling Insights From a Large‐Scale Tertiary Center Registry Analysis - Abolfazl Salari; Parvin Kalhor; Ahmad Vakili‐Basir; Houshang Bavandpour Karvane; Mina Pashang; Mojgan Ghavami; Arash Jalali; Farshid Alaeddini; Farzad Masoudkabir (Health Science Reports)
ABSTRACT Background and Aims The role of the atherogenic index of plasma (AIP) in predicting major adverse cerebro‐cardiovascular events (MACCE) after coronary artery bypass grafting (CABG) surgery has not been fully explored. The present study aims to investigate the prognostic value of AIP in predicting MACCE and its individual components following CABG. Methods This is a large‐scale retrospective study conducted on patients who underwent isolated CABG. The primary outcomes were all‐cause mortality and MACCE, which included acute coronary syndrome (ACS), Cerebrovascular accident (CVA)/transient ischemia attack (TIA), revascularization, and all‐cause mortality. Proportional Hazard (PH) Cox regression, considering stabilized Inverse probability weightings (IPW), was conducted after verifying the PH assumption. Results Totally, 23,432 patients analyzed with median 111.4‐month follow‐up duration. After weighting all variables, a higher AIP was associated with a significantly increased risk of MACCE (HR = 1.05; 95% CI: 1.01–1.09; p = 0.006). Furthermore, AIP was a significant predictor of the risk of revascularization (HR = 1.15; 95% CI: 1.01–1.30; p = 0.034) and ACS (HR = 1.09; 95% CI: 1.01–1.17; p = 0.020). However, AIP couldn't be a prognostic factor for all‐cause mortality and CVA. Conclusion AIP predicts MACCE, revascularization, and ACS after CABG, serving as a readily accessible prognostic factor.